Patient-reported Data as Predictors of Surgical Outcome in Patients With Degenerative Cervical Myelopathy: Analysis of a National Multicenter Dataset. Issue 2 (15th January 2023) - Gerdhem, Lovisa; Charalampidis, Anastasios; Gerdhem, Paul
Abstract : Study Design: Retrospective study design on prospectively collected registry data. Objective: To investigate whether improvement after surgery for degenerative cervical myelopathy is associated with preoperative disease severity and to identify predictors of outcome. Summary of Background Data: Degenerative cervical myelopathy is the most common cause of spinal cord compromise in adults and surgery is often the treatment of choice. Identifying predictors may help to improve patient selection. Materials and Methods: This nationwide study from the Swedish spine registry included 901 patients treated surgically for degenerative cervical myelopathy. To investigate improvement in different disease severity groups, the individuals were divided into quartiles based on their preoperative European Myelopathy Scale (EMS) and EuroQol-5 Dimension (EQ-5D) index. Statistical analyses were made with analysis of variance, χ 2, McNemar, and t tests. Multivariable linear or logistic regression was used to identify predictors for one-year improvement in EMS and EQ-5D index, and satisfaction at one year. In the regressions, the patient-reported outcome measures were dichotomized at their median, except improvement in EMS. Results: All patient-reported outcome measures improved from baseline to the one-year follow-up ( P <0.001). Statistically significant outcome improvements were seen in all disease severity groups. Preoperative low EMS (β=−1.37, P <0.001), long walking distance (<500 vs. >500 m; β=0.44, P =0.030), and low NDI (β=−0.43, P =0.048) were independent predictors of improvement in EMS. R 2 was 0.11 for the multivariable model. Preoperative low EQ-5D index (odds ratio=0.11; 95% confidence interval: 0.07–0.16) and low NDI (0.56; 0.36–0.88) were independent predictors of improvement in EQ-5D index. Preoperative high EMS (1.86; 1.20–2.90) and shorter arm pain duration [<12 vs. >12 months (0.54; 0.33–0.88)] were independent predictors of satisfaction. Conclusions: Postoperative improvement was seen over the whole range of disease severity. Disease severity, symptom duration, and walking distance were predictors of outcome in patients treated surgically for degenerative cervical myelopathy. Level of Evidence: III.